2014
DOI: 10.1017/s1368980014002936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Balanced Menus Challenge: a healthy food and sustainability programme in hospitals in Maryland

Abstract: Objective: The Balanced Menus Challenge (BMC) is a national effort to bring the healthiest, most sustainably produced meat available into health-care settings to preserve antibiotic effectiveness and promote good nutrition. The present study evaluated the outcomes of the BMC in the Maryland/Washington, DC region. Design: The BMC is a cost-effective programme whereby participating hospitals reduce meat purchases by 20 % of their budget, then invest the savings into purchasing sustainably produced meat. A mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…High-fat processed food, the use of non-nutritive additives, meat produced using antibiotics and hormones, obesity, antibiotic resistance, diabetes, cancer, food waste, and pollution caused by food transport are among the problems that current food systems face [88,89,91,92]. Hospitals have the potential to impact sustainability by addressing food issues, given their role as intermediaries in the market, their buying power, their responsibility for the promotion of proper nutritional habits, and the large number of people who frequent these organizations, between patients, visitors, employees, and the community [93].…”
Section: Food Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…High-fat processed food, the use of non-nutritive additives, meat produced using antibiotics and hormones, obesity, antibiotic resistance, diabetes, cancer, food waste, and pollution caused by food transport are among the problems that current food systems face [88,89,91,92]. Hospitals have the potential to impact sustainability by addressing food issues, given their role as intermediaries in the market, their buying power, their responsibility for the promotion of proper nutritional habits, and the large number of people who frequent these organizations, between patients, visitors, employees, and the community [93].…”
Section: Food Managementmentioning
confidence: 99%
“…Reference [93] identifies 12 opportunities through which food practices may be addressed: procurement, catering contracts, menu development, pricing, waste management, infrastructure, staff training, information, education, communication and feedback, partnerships, and special events. Similarly, Reference [91] suggests practices that range from the participative design of new options with staff and customers to behavioral initiatives that encourage the consumption of healthier food, while Reference [92] shows that reducing meat consumption by up to 20% and substituting it for vegetarian or alternative proteins from local sources is feasible for hospitals, without a detriment to budgetary increases.…”
Section: Food Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this centralised model provides opportunities for change at scale, and advantages in terms of food quality, consistency, choice and reduction in waste, identifying the key levers may be difficult for single organisations. For example, replication of the Balanced Menus Challenge, a US-based effort to bring sustainably produced meat available into healthcare settings whereby participating hospitals reduce meat purchases by 20% of their budget, then invest the savings into purchasing sustainably produced meat, 27 could be effectively implemented at scale should the right drivers be identified. One respondent suggested that local place-based central meal preparation facilities working across sectors might be a way forward.…”
Section: Discussionmentioning
confidence: 99%
“…Physical environments In the context of this special issue, the physical environments level of analysis grouped those papers that investigated the changing of practices in hospital, public kitchen and educational institutional settings, as well as community-based interventions. Ranke et al evaluated the outcomes of the Balanced Menus Challenge in which participating US hospitals reduce meat purchases by 20 %, then invest the savings into purchasing sustainably produced meat (17) . The study demonstrates that hospitals in the Maryland/Washington, DC region can reduce meat purchasing and increase the amount of sustainably produced meat purchased and served.…”
Section: Macro-level Environmentsmentioning
confidence: 99%